Cross Sector Data Sharing: Necessity, Challenge, and Hope. (2019) - Schmit, Cason; Kelly, Kathleen; Bernstein, Jennifer
Abstract : Existing data sources have tremendous potential to inform public health activities. However, a patchwork of data protection laws impede data sharing efforts. Nevertheless, a data-sharing initiative in Peoria, IL was able to overcome challenges to set up a cross-sectoral data system to coordinate mental health, law enforcement, and healthcare services.